Incidence of upper gastrointestinal haemorrhage in Maori and New Zealand European ethnic groups, 2001–2010. Issue 8 (August 2014) - Irwin, J.; Ferguson, R.; Weilert, F.; Smith, A.
Abstract Background To date no incidence figures for upper gastrointestinal haemorrhage (UGIH) in New Zealand have been published. Aims To determine the incidence of UGIH in a demographically defined population, and to assess variation in incidence associated with demographic parameters. Methods Between 17 March 2001 and 12 October 2010, all patients presenting to Waikato Hospital with UGIH were prospectively ascertained, and clinical, epidemiological and laboratory data were collected. Incidence rates were calculated, and were age adjusted to the World Health Organization world standard population. Parameters associated with trends in incidence were examined. Results There were 1360 UGIH events, yielding a crude incidence of 59.2 per 100 000 adults (age ≥ 15 years) per year (all quoted incidence figures per 100 000 adults per year), and an age‐adjusted incidence (AAI) of 46.4. AAI was higher for Maori compared with New Zealand Europeans (91.3 vs 37.0, rate ratio (RR) = 2.47, P < 0.001). Maori were more likely to have a gastric ulcer at endoscopy (odds ratio (OR) = 2.21, P < 0.001). For those tested for Helicobacter pylori (n = 702), Maori were more likely to be infected (OR = 2.12, P < 0.001). AAI was higher for males (61.1 vs 33.6, RR = 1.82, P < 0.001). Males were more likely to have a duodenal ulcer at endoscopy (OR = 1.79, P < 0.001). AAI incidence decreased from the first to the second half of the study period (53.6 vs 45.8, RR = 1.17, P < 0.001). Conclusion AAI of UGIH in the Waikato region was 46.4. This was significantly higher in Maori and in males, and decreased over the study period. These data will provide a comparison for future assessment of trends in UGIH.